Impact of movement tempo distribution on bar velocity during a multi-set bench press exercise - Trybulski, R.; Jarosz, J.; Krzysztofik, M.; Filip-Stachnik, A.; Matykiewicz, P.; Zmijewski, P.; Bichowska, M.; Wilk, M. (Journal of Human Kinetics, 2021)
The goal of the present study was to evaluate the effect of contrast tempo movement on bar velocity changes during a multi-set bench press exercise. In randomized and counter-balanced order, participants performed three sets of the bench press exercise at 60%1RM under two testing conditions: E-E where all repetitions were performed with explosive (X/0/X/0) movement tempo; and S-E where the first two repetitions were performed with a slow tempo (5/0/X/0) while the third repetition was performed with explosive movement tempo (slow, slow, explosive). Twelve healthy men volunteered for the study (age = 30 ± 5 years; body mass = 88 ± 10 kg; bench press 1RM = 145 ± 24 kg). The three-way repeated measures ANOVA (tempo × set × repetition) showed statistically significant multi-interaction effect for peak bar velocity (p < 0.01; Eta2 = 0.23), yet not for mean bar velocity (p = 0.09; Eta2 = 0.14). The post hoc results for multi-interaction revealed that peak bar velocity in the 3rd repetition was significantly higher for E-E compared to SE only during set 1 (p < 0.001). Therefore, the distribution of movement tempo had a significant impact on peak bar velocity, but not on mean bar velocity. The decrease in peak bar velocity in the 3rd repetition during the S-E condition was observed only in the first set, while such a tendency was not observed in the second and third set.